An Asian case of combined 17α-hydroxylase/17,20-lyase deficiency due to homozygous p.R96Q mutation: A case report and review of the literature - Liao, Qian; Shen, Rufei; Liao, Mingyu; Ran, Chenxi; Zhou, Ling; Zhang, Yuling; Peng, Guiliang; Sun, Zheng; Zheng, Hongting; Long, Min (Frontiers in Endocrinology, 2022)
Background：Combined 17α-hydroxylase/17,20-lyase deficiency (17-OHD) is a very rare form of congenital adrenal hyperplasia (CAH) caused by mutations in the CYP17A1 gene. Almost 100 different mutations of the CYP17A1 gene have been reported, including p.R96Q mutation, but no case of p.R96Q mutation has been described in Asian populations. Case Presentation: We describe a 22-year-old female patient of 46,XY karyotype, who presented with pseudohermaphrodism, primary amenorrhea, underdeveloped secondary sexual characteristics, delayed epiphyseal healing, hypertension and hypokalemia. The diagnosis of 17α-hydroxylase/17,20-lyase deficiency was reached by measurement of steroid hormones and abdominal CT scan, and confirmed by genetic sequencing, which revealed a homozygous p.R96Q missense mutation in the CYP17A1 gene. The patient received treatment with dexamethasone and estradiol, and 4 months of follow-up showed that both blood pressure and potassium were well controlled. Conclusions: This is the first Asian case of CAH caused by a homozygous p.R96Q missense mutation in the CYP17A1 gene. Herein, we highlight the role of inguinal hernia in the early diagnosis of female 17-OHD, and the necessity of removing the ectopic testis.